Superior energy storage performance coupled with excellent electrical characteristics in lead-free Ba0.8Ca0.2TiO3-(Bi0.80Mg0.20) (Ti0.65Mg0.30)O3 ceramics. (21st September 2021) - Jain, Aditya; Kumar, Ajay; Gupta, Neha; Kumar, Vinay
Abstract: Multi-layer ceramic capacitors with high recoverable energy storage density and large energy efficiency play a crucial in modern electronic devices. Various ferroelectric ceramic materials with relaxor characteristics and large dielectric constant are the most favorable candidates for achieving superior energy storage performance. Herein, a novel lead-free (1− x )Ba0.80 Ca0.20 TiO3 - x (Bi0.80 Mg0.20 )(Ti0.65 Mg0.30 )O3 (BCT-BMT) ceramic materials were prepared by two-stage mechano-chemical activation technique. BMT substitution in Ca modified BaTiO3 has resulted in substantial improvement in microstructural characteristics and subsequently an improvement in energy storage performance in comparison to pure BCT. The introduction of BMT in BCT has resulted in transformation into relaxor ceramics, which is vital for obtaining high recoverable energy storage density and large energy efficiency. In the present investigation, the composition with 0.65BCT-0.35BMT shows a typical relaxor characteristic, large breakdown strength, and a substantially large dielectric constant. As a result of improvement in electrical properties, the composition 0.65BCT-0.35BMT possesses an ultra-high recoverable energy density of 3.09 J cm −3 along with a moderately high energy efficiency of ∼80.15%. The obtained results indicate the effectiveness of BMT substitution on the energy storage properties and excellent compatibility between BCT and BMT phases.